Non-Monotonous Logic Model of the Clp-Usd Exchange Rate: An Approach from Artificial Neural Networks (Ann) - Vasquez-Perez, O; Rojo-Gonzalez, L (Institute of Electrical and Electronics Engineers Inc., 2018)
In this work we propose a forecast model of the variation of the sign between exchange rate Chilean peso and American dollar (CLP-USD) at the close of two consecutive exchange days. This model is based on feedforward Artificial Neural Network development, whose structure considers a set of explanatory premises to describe the exchange behavior under study in a non-monotonous logical setting. The exchange rate CLP-USD at the beginning, at the closure, minimum and maximum values obtained during an exchange day from January 1, 2005 to July 9, 2018 are used. The obtained results show a good and robust percentage of sign prediction in different extra samples. © 2018 IEEE.
Keywords: Artificial Neural Network; Exchange rate; Forecast; Non-monotonous logical